Antenatal diagnosis of spontaneous fetal bladder rupture presenting as progressive urinary ascites secondary to posterior urethral valves: a case report - G., Shiny Nivya; K., Vidhya Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Fetal urinary ascites is a rare antenatal finding most commonly associated with lower urinary tract obstruction, particularly posterior urethral valves (PUV). Spontaneous fetal bladder rupture leading to urinary ascites represents a protective “pop-off” mechanism that may reduce intrarenal pressure and preserve renal function. Antenatal differentiation of urinary ascites from hydrops fetalis is crucial, as prognosis and management differ significantly. We report a case of progressive fetal urinary ascites detected at 29 weeks of gestation, characterized by increasing ascites, a persistently collapsed bladder, and evolving oligohydramnios on serial ultrasonography. Fetal MRI at 35 weeks demonstrated a 4-mm defect in the anterior bladder wall with associated hydroureteronephrosis, confirming antenatal bladder rupture. The neonate was diagnosed postnatally with urinary ascites and PUV on micturating cystourethrogram, and underwent successful valve ablation followed by vesicostomy, with favourable renal outcome. This case highlights the importance of meticulous serial sonographic surveillance, the complementary role of fetal MRI in confirming bladder wall defects, and the value of coordinated perinatal management in improving neonatal prognosis in foetuses with urinary ascites secondary to bladder rupture.